Studi Kritis Hadits-Hadits Kepemimpinan (Imamah) Dua Belas Imam dalam Literatur Hadits Sunni - Zaki, Muhammad (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2017)
The imamah (leadership) of twelve imams is considered as a concept coming from Shi’ite tradition. Hadith literature of Sunni, however, has numerous hadith on imamah as exemplified by Shahih Bukhari, Muslim, Sunan Abi Dawud, al-Tirmidzi, al-Nasa’i, Ibn Majah, and Musnad Imam Ahmad. Although these hadith have some differences in terms of their structure, the hadith have in common in their meaning and substance. Sunni scholars consider the quality of transmitters and content of hadith on twelve imams is shahih. In contrast, Shi’ite scholars do not consider them as mutawatir. Sunni scholars of hadith are not in agreement in determining the figures considered as a twelve imam. However, they agree that all the twelve imams were from Quraish tribe and sworn in by ummah. The restriction of some imams to twelve is not absolute since there is a hadith stating that the number of imam and caliphate would emerge after the death of the Prophet saw. Muslim were obliged to put their loyalty on and obey them. The name of twelve imams derives from the fact that during their leadership, Muslims achieved the glorious period in terms of religious, scientific and political field.